Avoiding Pitfalls of Tibiotalocalcaneal Nail Malposition With Internal Rotation Axial Heel View. Issue 6 (December 2018) - Callahan, Ryan; Juliano, Paul; Aydogan, Umur; Clayton, Justin
Background . Tibiotalocalcaneal (TTC) nails are often used for complex hind foot arthrodesis and deformity correction. The natural valgus alignment of the hindfoot creates a challenge to optimum placement of the guidewire and eventual nail with a straight or valgus-curved nail. Methods . Five fresh frozen cadavers were used for placement of a TTC guidewire with standard anterior-posterior (AP), lateral, and Harris axial heel views as a reference for proper placement. The limb was then rotated 15°, 30°, and 45° both internally and externally to evaluate the perceived amount of osseous purchase within the calcaneus. The TTC nail was then inserted and dissection was performed to demonstrate proximity of the nail to the sustentaculum tali and neurovascular structures. Results . A 30° internal rotation Harris axial heel view demonstrated the most accurate representation of osseous purchase within the calcaneus with the guidewire and nail placement. When the guidewire was placed with standard imaging the nail was often ultimately placed in close proximity to the sustentaculum tali and neurovascular structures. Conclusion . Careful placement of the guidewire prior to reaming and nail placement should be undertaken to avoid neurovascular injury and to increase osseous purchase. For optimal guidewire placement, the authors suggest using appropriate anatomic landmarks and using a 30° internally rotated Harris axial heel view to verify correct placement. Levels of Evidence: Level V: Expert opinion